Evaluation of Service Life of Polystyrene in Tropical Marine Environment by Principal Component Analysis - Dongdong Song; Jin Gao; Lin Lu; Xiaogang Li (Advances in Materials Science and Engineering)
To predict the service life of polystyrene (PS) under an aggressive environment, the nondimensional expression Z was established from a data set of multiple properties of PS by principal component analysis (PCA). In this study, PS specimens were exposed to the tropical environment on Xisha Islands in China for two years. Chromatic aberration, gloss, tensile strength, elongation at break, flexural strength, and impact strength were tested to evaluate the aging behavior of PS. Based on different needs of industries, each of the multiple properties could be used to evaluate the service life of PS. However, selecting a single performance variation will inevitably hide some information about the entire aging process. Therefore, finding a comprehensive measure representing the overall aging performance of PS can be highly significant. Herein, PCA was applied to obtain a specific property (Z) which can represent all properties of PS. Z of PS degradation showed a slight decrease for the initial two months of exposure after which it increased rapidly in the next eight months. Subsequently, a slower increase of Z value was observed. From the three different stages shown as Z value increases, three stages have been identified for PS service life.